Antibacterial activity of cutting-edge dental crown materials - Baptista, Inês de Oliveira (2022)
Dental plaque is formed by thousands of bacteria dispersed in a matrix of salivary glycoproteins and extracellular polysaccharides that are difficult to remove from hard intraoral surfaces. Due to the resistance of bacteria to antibiotics, excessive dental plaque causes pulp necrosis, periapical gingivitis, and periodontitis. Currently, the most used dental crowns to replace natural teeth are lithium disilicate. This category of glass-ceramic presents colour, light transmission, transparency, and natural-looking shadows, ensuring an aesthetic behaviour identical to the one found on the tooth. In addition to these characteristics, it has adequate mechanical properties to prevent severe wear due to chewing and speaking. The objective of this work is to produce and characterize various compositions of glass and glass-ceramics that have, in their composition, ions described as antibacterial - zinc and cerium - in order to develop materials for dental crowns with antibacterial activity, which prevent the adhesion of bacteria to the restorations’ surface. Considering the results obtained, the crystallographic analyses revealed that, generally, phases of lithium metasilicate, lithium disilicate, cristobalite, lithium phosphate and cerium were precipitated. The microhardness and fracture toughness values obtained are similar to those presented by the commercial material used as reference (IPS e.max CAD), ~ 5.80 GPa and 2.0 MPa.m1/2, respectively. The mechanical properties are due to the micrographs presented, which show that the lithium disilicate crystals have an acicular morphology. The addition of ceria oxide promoted the precipitation of cerium crystals, responsible for the exceptional optical properties. In the study of antibacterial properties, the compositions Zero and C (which contain lithium, phosphate, potassium and - in the case of composition C - cerium ions) were the most promising, showing lower optical density values than the control, demonstrating bactericidal action. Chemical analysis of the solutions incubated with the glasses and glass-ceramics for 24 and 48 h showed leaching of lithium and cerium ions, which are generally attributed to an important role in antibacterial activity.